2016
DOI: 10.1167/iovs.15-17551
|View full text |Cite
|
Sign up to set email alerts
|

Graft Site Microenvironment Determines Dendritic Cell Trafficking Through the CCR7-CCL19/21 Axis

Abstract: PurposeThe graft site microenvironment has a profound effect on alloimmunity and graft survival. We aimed to study the kinetics and phenotype of trafficking antigen-presenting cells (APC) to the draining lymph nodes (DLNs) in a mouse model of corneal transplantation, and to evaluate the homing mechanisms through which graft site inflammation controls APC trafficking.MethodsAllogeneic donor corneas were transplanted onto inflamed or quiescent graft beds. Host- (YAe+) and donor (CD45.1+ or eGFP+)-derived APCs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…The detected transcripts encoded chemokines ( CCL‐3, CCL‐4, CCL‐5, CCL‐19, CCL‐20 and CCL‐21 ), cytokines ( IL‐2, IFN‐γ, TNF‐α and GM‐CSF ) and immune modulating factors in the tumour microenvironment (VEG‐F, SDF‐1, FAP, MMP‐9, IL‐10 and PDL‐1) . Primers and other details have been described in previously published reports by our group and others . qRT‐PCR data were analysed using the comparative Ct method, and expression levels of target genes were normalized to β‐actin levels in each tissue sample.…”
Section: Methodsmentioning
confidence: 99%
“…The detected transcripts encoded chemokines ( CCL‐3, CCL‐4, CCL‐5, CCL‐19, CCL‐20 and CCL‐21 ), cytokines ( IL‐2, IFN‐γ, TNF‐α and GM‐CSF ) and immune modulating factors in the tumour microenvironment (VEG‐F, SDF‐1, FAP, MMP‐9, IL‐10 and PDL‐1) . Primers and other details have been described in previously published reports by our group and others . qRT‐PCR data were analysed using the comparative Ct method, and expression levels of target genes were normalized to β‐actin levels in each tissue sample.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have alluded to the role of DCs as biomarkers for corneal epithelial inflammation in patients with type 2 diabetes mellitus, suggesting they may also be used as biomarkers for graft-related inflammation [56]. Nuanced variations in the presence, phenotype, and maturity of APC and DC populations have been shown to have varying associations on corneal allograft transplantation outcomes, implying they may reveal underlying immune dynamics [16,57,58]. Hamrah et al reported that the number and distribution of mature CD11c+ DC populations is increased in the anterior stroma and that there is an upregulation of MHC class II molecules within 24 h after inflammation is induced.…”
Section: Major Histocompatibility Complex and Antigen-presenting Cellsmentioning
confidence: 99%
“…However, current methods used to stimulate lymphangiogenesis require an inflammatory insult, which in and of itself may trigger augmented DC migration. Work from our group and others helped to reveal the role of CC-chemokine receptor 7 (CCR7) in migration of corneal DCs to the lymph nodes 29, 46, 65, 66, 67, 68 , which could be another way that DC migration may be regulated independently of lymphangiogenesis 66 . Corneal abrasion was also demonstrated to increase antigen drainage to the lymph nodes, signifying a key role for the epithelium in maintaining immune privilege 69 .…”
Section: Eye Immune Privilege Breach and The Mpsmentioning
confidence: 99%